Engineering Cocatalysts onto Low‐Dimensional Photocatalysts for CO2 Reduction. Issue 10 (3rd July 2021) - Di, Jun; Lin, Bo; Tang, Bijun; Guo, Shasha; Zhou, Jiadong; Liu, Zheng
Abstract : Low‐dimensional semiconductors are regarded as alternative architectures to achieve high‐efficiency photocatalytic CO2 reduction activity due to the unique structural and electronic properties. However, the catalytic efficiency is still limited by two factors, namely, poor surface charge separation efficiency and lack of surface‐active sites for CO2 reduction. Herein, the state‐of‐the‐art progress of cocatalysts engineering is reviewed to ameliorate these issues, to acquire outstanding behavior. The fundamentals of cocatalysts for CO2 photoreduction along with some noteworthy points are presented. The strategies of engineering cocatalysts for performance optimization are summarized with the emphasis on structure–performance correlations, such as component engineering, phase engineering, facet engineering, size engineering, single‐atom engineering, crystallinity engineering, defect engineering, strain engineering, and interface engineering. Finally, this review is ended with an outlook on unsolved issues and perspectives over cocatalysts modified low‐dimensional photocatalysts. Abstract : Recent progress in the research and development of cocatalysts design to boost the performance of low‐dimensional photocatalysts for CO2 reduction is reviewed. The different strategies of engineering cocatalysts for performance optimization are summarized with the emphasis on structure–performance correlations.